2018
DOI: 10.15576/gll/2018.4.29
|View full text |Cite
|
Sign up to set email alerts
|

A short review of interpolation methods used for terrain modeling

Abstract: The determination of landforms of the terrain depends on a number of procedures. In general, all these procedures can be subdivided into two groups. The first group consists of measurement activities related to obtaining real-life data. The second group comprises operations related to the processing of results, in order to obtain the imaging. The measurements of the terrain and its landforms are discrete. Cartographic images are continuous. In order to get a map of 3D measurements, contours need to be interpol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The global polynomial interpolation fits a mathematically derived surface to the entire study area based on all observed data points [146,149], as shown in Figure A1A. GPI is suitable for slowly varying parameters [52].…”
Section: -2017mentioning
confidence: 99%
“…The global polynomial interpolation fits a mathematically derived surface to the entire study area based on all observed data points [146,149], as shown in Figure A1A. GPI is suitable for slowly varying parameters [52].…”
Section: -2017mentioning
confidence: 99%
“…The Global Polynomial Interpolation method involves fitting a smooth surface, defined by a mathematical function (polynomial), to the data points of the input [22]. The method of global polynomial interpolation is classified as an inaccurate interpolator because the mathematical function rarely passes through all the actual measured points.…”
Section: Global Polynomial Interpolationmentioning
confidence: 99%
“…It can be seen that Kriging is often chosen. It is flexible and includes many parameters, which can be both-positive, as it allows precise modeling, and negative, as using Kriging forces a detailed and relatively complicated data analysis, searching trends and modeling [22][23][24]. This causes more workload than in the case of other methods, but on the other hand, the faster analysis does not have to be more accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Upscaling soil GHG fluxes using the RF algorithm required spatial raster maps of the soil physico-chemical predictor parameters. Thus, we interpolated our measured point data to continuous landscape maps using the inverse distance weighted (IDW) approach in the System for Automated Geoscientific Analyses software (SAGA: QGIS) with a distance coefficient power of 1 (Gradka & Kwinta 2018). The spatial interpolations were performed per land use (forest, grassland, and arable land) and for each season (summer and autumn) due to significant variations in soil parameters such as soil moisture or inorganic N content across land uses and seasons (see Wangari et al, 2022).…”
Section: Spatial Interpolation Of Soil Parametersmentioning
confidence: 99%